The crime of human trafficking as a complex crime and its difficulties in the Peruvian jurisprudence - Montoya Vivanco, Yvan (2016)
The crime of human trafficking is a crime of complex nature and presents problems in its interpretation in the Peruvian law and jurisprudence. These problems require the author to study the legally protected goods behind this criminal prohibition, the consent of minors, analysis of the previous domain relationship above the victim or caused by the perpetrator, and the evidential approach that this reinterpretation of the crime of trafficking assumes. According to the previous legal framework, the author stands his proposal, which is characterized by criticism and being contrary to the Peruvian supreme jurisprudence.